Comparison between endocrown fracture resistance with post core crown - Krisna, Yohanes Paulus; Tanti, Ira (Indonesia Prosthodontic Association, 2020)
The concept of minimally invasive restoration has been more approached lately, with the aim of preserve the remaining tooth structure especially after endodotic treatment. Endocrown is one type of restoration that might be the solution. Endocrown is made of glass-ceramic material, defined as a single restoration that uses pulp cham-bers as a retention and resistance form, margin of preparation is above the gingiva in order to preserve tooth structure. Endocrown was initiated by Pissis in 1995 and popularized by Bindl and MÃ¶rmann in 1999. According to late research, crown endocrown has higher fracture resistance than post-core crown. Although the literature on endocrown is still limited, empirical evidence leads to positive view for the use of this restoration.